Ultrasound–Microwave Combined Extraction of Novel Polysaccharide Fractions from Lycium barbarum Leaves and Their In Vitro Hypoglycemic and Antioxidant Activities - Na Quan; Yi-Dan Wang; Guo-Rong Li; Zi-Qi Liu; Jing Feng; Chun-Lei Qiao; Hua-Feng Zhang (Molecules, 2023)
Ultrasound–microwave combined extraction (UMCE), gradient ethanol precipitation, chemical characterization, and antioxidant and hypoglycemic activities of Lycium barbarum leaf polysaccharides (LLP) were systematically studied. The optimal conditions for UMCE of LLP achieved by response surface method (RSM) were as follows: microwave time of 16 min, ultrasonic time of 20 min, particle size of 100 mesh, and ratio of liquid to solid of 55:1. Three novel polysaccharide fractions (LLP30, LLP50, LLP70) with different molecular weights were obtained by gradient ethanol precipitation. Polysaccharide samples exhibited scavenging capacities against ABTS and DPPH radicals and inhibitory activities against α-glucosidase and α-amylase. Among the three fractions, LLP30 possessed relatively high antioxidant and hypoglycemic activities in vitro, which showed a potential for becoming a nutraceutical or a phytopharmaceutical for prevention and treatment of hyperglycemia or diabetes.